The frequency of consanguineous marriage among British Pakistanis. Issue 3 (March 1988) - Darr, A; Modell, B
Abstract : An enquiry answered by 100 randomly selected British Pakistani mothers in the postnatal wards of two hospitals in West Yorkshire showed that 55 were married to their first cousins, while in only 33 cases had their mother been married to her first cousin. This suggests an increasing rate of consanguineous marriage in this relatively small group, by contrast with the decreasing rate observed in some other countries. The genetic implications merit further study.